FAMILY CONFLICTS AND METHODS OF THEIR MANAGEMENT - Fayzullayev Xurshidjon Shoakbar’s son (American Journals Publishing, 2023)
This article analyzes the theoretical and practical aspects of the causes of family conflicts and ways to eliminate family conflicts, the consequences of conflict situations, the impact on the development of society.
Keywords: Family conflicts, Marriage, Conflict, destructiveness and creativity, Aggression, Selfishness. Destructive constructive Compliance